Management of Internal Root Resorption on Permanent Teeth - Elisabeth Nilsson; Eric Bonte; François Bayet; Jean-Jacques Lasfargues (Hindawi Limited, 2013)
Internal root resorption (IRR) is a particular category of pulp disease characterized by the loss of dentine as a result of the action of clastic cells stimulated by pulpal inflammation. This review article explains the etiology, the prevalence of IRR, and, in addition to the clinical data, the contribution of the three-dimensional imaging (CBCT) to the diagnosis, the clinical decision, and the therapeutic management of IRR. The authors discussed the various therapeutic options including the orthograde or retrograde fillings of the root canal resorption area. Root canal treatment remains the treatment of choice of internal root resorption as it removes the granulation tissue and blood supply of the clastic cells. The authors describe with different clinical cases the modern endodontic techniques including optical aids, ultrasonic improvement of chemical debridement, and the use of alternative materials such as calcium silicate combined with thermoplastic filling (warm gutta-percha). In these conditions, the prognosis of the conservative treatment of internal resorptions, even if root walls are perforated, is good.